2000
DOI: 10.1111/j.1530-0277.2000.tb02052.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol‐Induced Up‐Regulation of Candidate Plasminogen Receptor Annexin II in Cultured Human Endothelial Cells

Abstract: These results demonstrated that low ethanol increased Ann-II antigen/mRNA levels and up-regulated Ann-II gene expression at the transcriptional level. The results further identify and define the contribution and role of the plasminogen receptor, Ann-II, in the ethanol-induced mechanism of increased EC fibrinolysis that may underlie and contribute, in part, to the cardioprotective benefit associated with moderate alcohol consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 64 publications
2
16
0
Order By: Relevance
“…ANXA2 was up-regulated in endothelial cells from cirrhotic ALD liver which is consistent with reports of ANXA2 over-expression in HUVEC cells in the presence of alcohol [12]. We found co-localization of ANXA2 with p11 (Fig.…”
Section: Alcohol and Anxa2 Mediated Fibrinolysis In Vitrosupporting
confidence: 94%
See 2 more Smart Citations
“…ANXA2 was up-regulated in endothelial cells from cirrhotic ALD liver which is consistent with reports of ANXA2 over-expression in HUVEC cells in the presence of alcohol [12]. We found co-localization of ANXA2 with p11 (Fig.…”
Section: Alcohol and Anxa2 Mediated Fibrinolysis In Vitrosupporting
confidence: 94%
“…ANXA2 is known to enhance plasmin generation and activation of clot dissolution in endothelial cells [9] and breast cancer cells [10]. A doubling of fibrinolytic activity with increased ANXA2 expression was reported at the surface of human vascular endothelial cells (HUVEC) on exposure to low levels of alcohol [11,12]. The cardioprotective role of low dose alcohol was thought to be mediated, at least in part, via potentiation of ANXA2 regulated fibrinolysis [11,12].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Alcohol induced up-regulation of annexin A2 was reported in endothelial cells [24]. Over-expression of annexin A2 and p11 in the liver in response to alcohol may regulate the production and degradation of plasmin and could modulate fibrinolysis, ECM degradation and fibrosis in ALD.…”
Section: Annexin A2 and P11mentioning
confidence: 97%
“…Similarly, Miyamoto et al (1999) demonstrated that alcohol augmented isoproterenol-stimulated t-PA gene expression and decreased PAI-1 messenger RNA (mRNA) levels in cultured human ECs. In concert, these alcohol-induced changes in fibrinolytic components result in increased fibrinolysis (Aikens et al, 1998;Tabengwa et al, 2000).…”
mentioning
confidence: 99%